Tadalafil therapy for erectile dysfunction following prostatectomy. (June 2015) - Kadıoğlu, Ateş; Ortaç, Mazhar; Dinçer, Murat; Brock, Gerald
Erectile dysfunction is a major complication affecting the quality of life of patients and partners after radical prostatectomy. Evolving evidence suggests that early penile rehabilitation may provide better erectile function after surgery. Phosphodiesterase type 5 (PDE-5) inhibitors are routinely considered a first-line treatment option in most algorithms for penile rehabilitation owing to their efficacy, ease of use, wide availability and minimal morbidity. Tadalafil is a long-acting, potent PDE-5 inhibitor for erectile dysfunction, with demonstrated effect in animal studies at preserving penile smooth muscle content and prevention of fibrosis of cavernosal tissue. This article evaluates the existing literature on tadalafil and critically analyzes its impact on erectile function following radical prostatectomy.